Retail Chains’ Strategies in Russia - ШерешеваМарина Юрьевна; КотельниковаЗоя Владиславовна; Radaev, Vadim; ТретьякОльга Анатольевна (Journal of Economic Sociology, 2011)
Detailed description in the text